A presença da Igreja Católica de Botucatu no Movimento Estudantil de 1968 - Zanin, Edmilson José (2024)
The present research, titled "The Presence of the Catholic Church of Botucatu in the Student Movement of 1968," had as its fundamental objective the analysis, within the historical context of the time, of the significance of the pacifying presence of the Catholic Church of Botucatu in the student movement in the city of Botucatu. Specifically, it focused on the interaction between the Church and the students of the Faculty of Medicine, who sought improvements in academic conditions and the allocation of funds essential for the implementation of a modern University Center. Faced with successive budget cuts by the government, these students called for a peaceful and demand-oriented strike of indefinite duration. To achieve this goal, original documentary sources were utilized, including correspondence, newspaper clippings, diaries, and reports produced by the Church, police, and students. Of particular significance was the oral source, obtained through interviews and testimonies. The analysis of these sources revealed that, despite the initial intention of the Botucatu student movement to focus on demands rather than politics, it was harshly persecuted and repressed by the military regime in power at the time. The younger priests of Botucatu, aligned with the new ideals of the Second Vatican Council and aware of the incompatibility between the totalitarian aspirations of the military and the principles of the Gospel, provided the students not only with full support but also with protection, sheltering them in the Seminary and in the churches when pursued by the police. It is important to highlight that, even in the face of violence, the students did not respond with aggression, demonstrating that the Botucatu student movement maintained its peaceful nature even when it took on political dimensions. The collection of this data was crucial for a more in-depth contextualization and a faithful representation of the events that occurred